Correlation between virulence gene expression and proton pump inhibitors and ambient pH in Clostridium difficile: results of an in vitro study - Stewart, David B.; Hegarty, John P. (Journal of medical microbiology, 2013)
Proton pump inhibitors (PPIs) are associated with the development of Clostridium difficile infection in humans. Though it is assumed that PPIs mediate this effect through gastric acid suppression, there has been little investigation into whether PPIs, or ambient pH, might directly affect the expression of C. difficile toxin genes. In the present study, C. difficile ribotypes 001, 027 and 078 obtained from human subjects were grown under anaerobic conditions prepared at pHs of 5, 7.3 and 9. Matched trios were exposed to 100 µM and 200 µM of omeprazole along with PPI untreated controls. Custom designed reverse transcription quantitative PCR hydrolysis probes were used to assess C. difficile gene expression for toxins A ( tcdA ), B ( tcdB ) and binary toxin ( cdtB ), as well as their positive regulators ( tcdR and cdtR ), using rrsA , which encodes 16S rRNA, as a constitutively expressed reference gene. tcdC and codY , negative regulators of toxin expression, were also assessed. Basic pH resulted in greater expression of tcdA , and with PPI exposure a 120-fold higher expression was noted with ribotype 001. tcdB and cdtB expressions were much less responsive to pH or PPIs, though a clear response to acidic pH and PPI exposure was observed in ribotype 027. tcdC and codY expressions were largely unaffected, except with ribotype 027; low pH and PPIs resulted in their greater expression, though to a lesser degree than with toxin genes and their positive regulators. Non-neutral pH and PPI exposure appear to have an effect on C. difficile , one that has a net effect towards toxin gene expression.